STRATEGIES OF AGENCY: ASSESSING THE INFLUENCE OF STATE FEMINISM ON MITIGATING GENDER-BASED VIOLENCE AGAINST WOMEN IN ITALY, FRANCE, AND SPAIN - Donato, Stellamarina (Cultura Latinoamericana, 2025)
This brief paper provides an extensive analysis of the role of state feminism in combatting genderbased violence against women, focusing on its implementation and impact in Italy, France, and Spain. The study examines the connection between state feminism—defined as the incorporation of feminist ideas and ideals into official procedures and policies—and the frequency and kinds of gender-based violence that take place in these countries. Gender-based violence is still a serious issue in France, Italy, and Spain, requiring extensive interventions. The evidence reveals that state feminism, when effectively integrated, is instrumental in fostering environments that condemn gender-based violence and promote gender equality. This initial comparative study contributes to a broader understanding of how governmental entities and feminist ideologies intersect to construct safer, more egalitarian societies.